2007
DOI: 10.1111/j.1440-1754.2007.01079.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of childhood asthma and control in children assessed in a pilot school‐based intervention programme in Singapore

Abstract: In Singapore, poor asthma control is found in a sizeable proportion of school children with asthma, is identifiable for high-risk groups of children from lower socio-economic backgrounds and having asthma-related attendance at the emergency rooms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…This is similar to other studies and has demonstrated poor asthma control among children, with the percentage of reported asthma symptoms ranging from 26% to 97.5%. 5,7,8,[15][16][17][18] These wide variations in the control of asthma among children could be due to different settings, populations, methods, and criteria used to define asthma control. For example, a study in 12 countries in Asia has reported inadequate asthma control in 97.5% of the children.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is similar to other studies and has demonstrated poor asthma control among children, with the percentage of reported asthma symptoms ranging from 26% to 97.5%. 5,7,8,[15][16][17][18] These wide variations in the control of asthma among children could be due to different settings, populations, methods, and criteria used to define asthma control. For example, a study in 12 countries in Asia has reported inadequate asthma control in 97.5% of the children.…”
Section: Discussionmentioning
confidence: 99%
“…15 In Singapore, Yang et al has reported approximately a quarter of school children with asthma were inadequately controlled. 8 The number of children with asthma included in that study was small (175), and only students of primary 1 and 6 were involved. Furthermore, the assessment of asthma control was based on the presence of asthma symptoms in the past 1 year.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations